2021
DOI: 10.1590/0001-3765202120190042
|View full text |Cite
|
Sign up to set email alerts
|

Gender Equality in Employment: A View from Kazakhstan

Abstract: Issue under consideration: existing legal resources to support gender equality in the workplace. We systematised the provisions of Kazakhstan labour law, which should guarantee the prohibition of discrimination based on sex. The analysis resulted in fi ve themes: "Characteristics of women's labour", "Analysis of labour laws differentiation", "Evaluation of labour rights discrimination" and "Characteristics of the new labour legislation of the Republic of Kazakhstan", "Characteristics of workers with a special … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…In working relations with the tripartite principle, it is not only the government that must be seen for its commitment, but also from the side of employers and workers. The same thing was found that these two actors did not have a good commitment in implementing gender equality policies [35]. Even though some women workers complained about discrimination, they were not fully responded to and followed up by both women workers through trade unions and by the leadership [9,36,37].…”
Section: Policy Implementation Analysis Based On Interviews With Info...mentioning
confidence: 90%
“…In working relations with the tripartite principle, it is not only the government that must be seen for its commitment, but also from the side of employers and workers. The same thing was found that these two actors did not have a good commitment in implementing gender equality policies [35]. Even though some women workers complained about discrimination, they were not fully responded to and followed up by both women workers through trade unions and by the leadership [9,36,37].…”
Section: Policy Implementation Analysis Based On Interviews With Info...mentioning
confidence: 90%
“…Адам саудасы проблемасына арналған А.Хамзина, Э. Бөрібаев және К. Сартаеваның (Khamzina, Buribayev&Sartayeva, 2022) ғылыми жарияланымында Қазақстандағы адам құқықтары жөніндегі уәкілдің қызметі туралы қоғамда ақпараттың жоқтығына назар аударылады [11]. Сарапшылар да Қазақстанда еңбек қатынастарында гендерлік теңдікті қамтамасыз ету мәселесі бар екенін мойындайды (Khamzina et al, 2021), бірақ олардың пікірінше, АҚУ бұған жеткілікті көңіл бөлмейді. Ең жиі кездесетін бұзушылықтаргендерлік кемсітушілік, жалақы теңсіздігі, кәсіби мүмкіндіктердің шектелуі [12].…”
Section: лн гумилев атындағыunclassified
“…The country implements a principle of equal gender rights, and thus, both sexes have equal access to education and equal business opportunities. However, women are still underrepresented in executive management positions [ 14 ]. The death rate is above the global average, and there is a striking discrepancy between life expectancy for men and women, which constitutes 67 and 77 years, respectively.…”
Section: Introductionmentioning
confidence: 99%